Salafi di Majlis Ta’lim Surabaya - Syafi’i, Imam (JOIES (Journal of Islamic Education Studies), 2021)
Salafis are language means ' those who preceded or life before the age of our' start to the prophet Muhammad, Companions , and Successors tabiit , to be guided by the Qur'an and Sunnah, the term Salafi adopted followers of Muhammad Abdullah ibn Wahhab to distinguish the term majlis taklim or study sunna , ulama or cleric sunna , the study of other not in their perspective considered toulama or cleric heresy even perverse, congregants are prohibited following the study were considered heretics. This Study focus on masjid Salafi at Jl. Botoh Putih 11 No. 17 and at Masjid Jami’ Bendul Merisi Surabaya. This Study find how salafi use the Islamic traditional term in Indonesia majlis taklim as their program to campaign their salafi perspective to the large audiences.